2000
DOI: 10.1046/j.1365-2222.2000.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of linkage between chromosome 5q23–33 markers and IgE/bronchial hyperreactivity in 67 Scottish families

Abstract: This study presents evidence against the presence of a gene with a major effect on total serum IgE or BHR in the 5q23-33 region, in this ethnic group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Similarly, the amounts of IL‐9 secreted by ex vivo stimulated T cells correlated with serum IgE in atopic infants . In agreement with a functional link to IgE production, some but not all studies have found an association of IL9 SNPs with serum IgE . Ongoing studies will hopefully define additional correlations of Th9 function with human physiology.…”
Section: What Can Th9 Cells Do?mentioning
confidence: 73%
“…Similarly, the amounts of IL‐9 secreted by ex vivo stimulated T cells correlated with serum IgE in atopic infants . In agreement with a functional link to IgE production, some but not all studies have found an association of IL9 SNPs with serum IgE . Ongoing studies will hopefully define additional correlations of Th9 function with human physiology.…”
Section: What Can Th9 Cells Do?mentioning
confidence: 73%
“…However, some studies failed to detect any linkage between chromosome 5q23–33 markers and IgE, BHR and asthma in isolated Finnish, Scottish and Hutterites families (Laitinen et al ., 1997; Mansur et al ., 2000; Ober et al ., 2000). However, in these studies environmental factors were not considered when evaluating the interaction effects of IL‐9 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Heritability of BHR has been estimated at about 30% [Palmer et al, 2000]. Evidence of significant associations between asthma with BHR and the ADAM33 region of chromosome 20p13 [van Eerdewegh et al, 2002], and between BHR independent of atopy and specific GSTP1 polymorphisms at 11q13 [Fryer et al, 2000] has been reported, however, results related to BHR and markers at 5q have been conflicting [Postma et al, 1995; Mansur et al, 2000]. No studies, to our knowledge, have used segregation analysis and found statistical corroboration of a major gene controlling BHR.…”
Section: Discussionmentioning
confidence: 99%
“…Linkage analysis of the affected sib pairs showed evidence of linkage between BHR and several genetic markers (D5S436, D5S658, D5S393, and FGFA) at 5q31‐33. In contrast, Mansur et al [2000] found no evidence for linkage between BHR and any 5q23‐31 markers in symptomatic and asymptomatic probands selected from a community sample. Fryer et al [2000] used trend analysis to look at the proportion of subjects with specific glutathione S‐transferase GSTP1 genotypes (on chromosome 11q13) in each of four BHR groups, ranging from non‐responsive to severe BHR.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation